2005
DOI: 10.1096/fj.05-4216fje
|View full text |Cite
|
Sign up to set email alerts
|

Mouse intestinal cryptdins exhibit circadian oscillation

Abstract: The innate immunity utilizes a plethora of antibacterial polypeptides, known as defensins, to combat ingested bacteria. Mouse enteric defensins (cryptdins) are produced and secreted constitutively but are overexpressed in instances of infection and/or inflammation. Our objective was to determine whether the biological clock plays a role in cryptdin expression under healthy conditions. Analysis of cryptdin 1 and cryptdin 4 expression in the ileum and jejunum of the small intestine of FVB/N mice around the circa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 49 publications
2
25
0
1
Order By: Relevance
“…Nutrition factors, such as food intake, appetite and digestion, have an effect on circadian patterns [36]. Food intake modulates the circadian rhythms, especially in liver and intestine [37,38] and misalignment of circadian rhythm leads to insulin resistance and diabetes [39,40]. In fact, skipping breakfast, one of the irregular eating, is associated with metabolic syndrome, diabetes and cardiovascular disease [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition factors, such as food intake, appetite and digestion, have an effect on circadian patterns [36]. Food intake modulates the circadian rhythms, especially in liver and intestine [37,38] and misalignment of circadian rhythm leads to insulin resistance and diabetes [39,40]. In fact, skipping breakfast, one of the irregular eating, is associated with metabolic syndrome, diabetes and cardiovascular disease [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Clock is more important than the presence of food in the intestinal lumen in the regulation of intestinal transport proteins. cryptidins ( 62 ) and most of the toll-like receptors ( 13 ) show circadian oscillations in the jejunum. Although we did not do a comprehensive systemic study, our sampling of critical intestinal functional proteins surprisingly revealed that several nutrient transport proteins show circadian expression and their expression is absent in Clk mt/mt .…”
Section: Clock Modulates Macronutrient Absorption By Regulating Transmentioning
confidence: 98%
“…Samples were embedded in optimal cutting temperature compound, rapidly frozen in liquid nitrogen, and stored at Ϫ 80°C. Frozen sections were cut with a cryostat (8 by guest, on May 12, 2018 www.jlr.org Downloaded from before or at the time of food availability, whereas Cry1 , Cry2, and Bmal1 levels increased 4 h later. In Clk mt/mt mice, however, these changes were not seen.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was DNAse I-treated using RQ1 DNAse (Promega, Madison, WI) for 2 hr at 37°, as was previously described. 27,28 Then 2 lg of DNAse I-treated RNA was reverse-transcribed using Moloney murine leukaemia virus (MMuLV) reverse transcriptase (Promega) and random hexamers. A 1/20 aliquot of the reaction was then subjected to quantitative real-time PCR using the Sybr Green Master kit (Applied Biosystems) and the ABI Prism 7300 Sequence Detection System (Applied Biosystems).…”
Section: Rna Extraction and Quantitative Real-time Polymerase Chain Rmentioning
confidence: 99%